PENINGKATAN KEMAMPUAN MEMBACA SISWA MELALUI METODE SINTAKSIS DAN MEDIA FLASH CARD - Rezqiana Anzhalni; Mohammad Afifulloh; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The background of the pandemic has made face-to-face education online and has an effect on declining student achievement. Students who are not accompanied when learning online will experience some changes in the academic field. Students who were originally fluent in reading, forgot letters and were less fluent in reading again.This research is located in Lawang with class 1 students as the subject and uses a class action research method which is discussed descriptively. Researchers are trying to improve students' reading skills by using a syntactic method and using flash cards. The results of this study are the achievement of indicators of student reading success with a number of more than 85% of the 28 students in one class.